PRODUKSI MISELIUM Grifola frondosa (Dickson: Fries) Gray ISOLAT CIANJUR DAN BOBOT EKSTRAKNYA PADA MEDIUM MYPB DENGAN PENAMBAHAN BIJI BUNGA MATAHARI Helianthus annuus L. - Rizki Maulida; Nuniek Ina Ratnaningtyas; Slamet Priyanto (Scripta Biologica, 2014)
Grifola frondosa or maitake, not only can be used as a food ingredient but also as medicine. Other than nutrients, fruit body and mycelium of G. frondosa also contains bioactive compounds, such as terpenoids, alkaloids, flavonoids, and beta glucans extracellular polysaccharides (β-1,3 glucans and β-1,6 glucans). Extracellular polysaccharide harvested more often in mycelium form which is cultivated in liquid medium. Liquid medium which is commonly used for the growth of mycelium is MYPB (Malt Yeast Peptone Broth). Mycelium production on MYPB as a medium can be increased by adding additional ingredients, one of which is sunflower (Helianthus annuus L.). The treatment was the addition of sunflower seeds on medium MYPB. The main parameters were mycelium’s dry weight and the weight of raw extract of G. frondosa. Supporting parameters were final pH medium, extracellular polysaccharides (qualitatively), terpenoid, alkaloid, and flavonoid compounds in the raw extract of G. frondosa. The addition of 250 g/l sunflower seeds in the medium MYPB was the optimum treatment that can produce 1,379 g/100ml of mycelium and 0,299 g/100ml G. frondosa extracts.